2021
DOI: 10.3389/fcell.2021.646967
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stromal Cell-Sheets Sandwiched, Book-Shaped Acellular Dermal Matrix Capable of Sustained Release of Basic Fibroblast Growth Factor Promote Diabetic Wound Healing

Abstract: The management of diabetic wounds is a therapeutic challenge in clinical settings. Current tissue engineering strategies for diabetic wound healing are insufficient, owing to the lack of an appropriate scaffold that can load a large number of stem cells and induce the interaction of stem cells to form granulation tissue. Herein we fabricated a book-shaped decellularized dermal matrix (BDDM), which shows a high resemblance to native dermal tissue in terms of its histology, microstructure, and ingredients, is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Taking advantage of the enhanced gene expression of angiogenic growth factors and endothelial markers after ASC spheroid formation, the spheroid sheet composite system demonstrated enhanced expression of these angiogenesis-related factors relative to ASC sheet alone. Co-delivery with recombinant growth factors or gene transfection had been applied to circumvent this disadvantage of ASC sheet therapy previously [ 13 , 14 ]. In comparison with these maneuvers, our approach of combining ASC spheroids and sheets employed no exogenous biological or genetic material, thus significantly decreasing the regulatory hurdles for clinical translation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of the enhanced gene expression of angiogenic growth factors and endothelial markers after ASC spheroid formation, the spheroid sheet composite system demonstrated enhanced expression of these angiogenesis-related factors relative to ASC sheet alone. Co-delivery with recombinant growth factors or gene transfection had been applied to circumvent this disadvantage of ASC sheet therapy previously [ 13 , 14 ]. In comparison with these maneuvers, our approach of combining ASC spheroids and sheets employed no exogenous biological or genetic material, thus significantly decreasing the regulatory hurdles for clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that VEGF is a key regulator of the paracrine effects of ASCs [ 12 ], so decreased VEGF secretion may hinder the regenerative effects of ASC sheets for ischemic tissues. To address this shortcoming, ASC sheets were attached to FGF2-tethered decellularized dermal matrix to enhance their angiogenic potential [ 13 ]. In another study, ASC sheets were transfected to express VEGF to restore perfusion and protect ischemic tissues [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic ASCs treated diabetic wounds are shown to have a longer time of complete healing than healthy ASCs treated wounds, and shorter than non-treated wounds (37,48). Application of non-diabetic human-derived ASCs on diabetic rats showed the average time of wound closure and the healing area measured at the same time is significantly increased in normal ASCs treated rats than diabetic ASCs treated rats (32,33,46,49,61). Most studies evaluate the area of healing on 3, 7, 14 days after injuries.…”
Section: Effects Of Diabetes On Autologous Ascsmentioning
confidence: 96%
“…In addition, gene-modified scaffolds may be more targeted to specific pathological conditions. The combination of ASCs and acellular dermal matrix (ADM) can also enhance wound repair in diabetic mice models, in which ADM support the proliferation and growth of ASCs ( 61 , 77 ). Besides, artificial engineered scaffolds such as gelatin gel, artificial dermis, and porous polymer ultrathin films have been studied as ASCs delivering technologies ( 78 , 79 , 81 , 82 ).…”
Section: Clinical Progress Of Ascs In Treating Diabetic Woundsmentioning
confidence: 99%
See 1 more Smart Citation